RETRACTED: Package for data management of a telecommunication device in a monitoring system - Sokolova A.V.; Login E.V.; Mashkovtsev G.A.; Grishanov I.S. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001